2019
DOI: 10.1097/01.hs9.0000561692.51897.d9
|View full text |Cite
|
Sign up to set email alerts
|

S853 Successor: A Multicenter Retrospective Noninterventional Follow‐up Study in Patients With Sickle Cell Pain Crises Who Previously Participated in the Sustain Trial in the United States

Abstract: Background: Haemophilia A is caused by deficiency of Factor VIII (F.VIII), an essential blood-clotting cofactor. Prophylaxis or on-demand treatment with recombinant FVIII forms the current standard of care to prevent bleeding in Haemophilia A patients in the developed world. However, approximately 30% of severe haemophilia A patients develop inhibitory antibodies against F.VIII. Moreover, FVIII treatment requires venous access which is burdensome. The recent successful clinical trials and subsequent regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another trial (the SUCCESSOR trial) retrospectively assessed the subsequent occurrence of VOCs in patients who completed the SUSTAIN study. This study reported that patients previously treated with crizanlizumab (5 mg/kg) maintained a similar time to first VOC compared with the same measurement while on treatment in SUSTAIN, suggesting a prolonged effect of crizanlizumab 24 . The abstract was presented at the 24th European Hematology Association Congress in 2019.…”
Section: Resultsmentioning
confidence: 75%
“…Another trial (the SUCCESSOR trial) retrospectively assessed the subsequent occurrence of VOCs in patients who completed the SUSTAIN study. This study reported that patients previously treated with crizanlizumab (5 mg/kg) maintained a similar time to first VOC compared with the same measurement while on treatment in SUSTAIN, suggesting a prolonged effect of crizanlizumab 24 . The abstract was presented at the 24th European Hematology Association Congress in 2019.…”
Section: Resultsmentioning
confidence: 75%
“…A multicenter, retrospective, non-interventional study (SUCCESSOR) followed up on the SUSTAIN study participants. Follow-up data report similar results, where VOCs increased after the trial compared to when receiving the intervention [51]. However, beyond this, few studies evaluating its real-world effectiveness have been completed, and many ongoing studies on crizanlizumab continue to investigate its safety and efficacy.…”
Section: Crizanlizumab-tmca (Adakveo)mentioning
confidence: 77%
“…Median time to first vaso-occlusive crises after treatment discontinuation was 6.1 months in the high-dose crizanlizumab-tmca group, 2.7 months in the low-dose crizanlizumab-tmca group, and 2.6 months in the placebo group. 14 Limitations: The study lacks long-term data and data in patients younger than 16 years. Several ongoing studies have been initiated to further assess crizanlizumab-tmca.…”
Section: Comparative Efficacymentioning
confidence: 99%